Kajian Kualitas Air Pasca-Pengerukan Alur Pelayaran Batu Kapur Sungai Donan Cilacap - Yogi Pamungkas; Sidharta Sahirman; Moh. Husein Sastranegara (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2014)
Donan River dredging impacts on ecological regions and communities around the basin. Dredging from Buoy 27 to Buoy segment 34 as an effort to reduce silting of existing in Cilacap and Donan River shipping channel maintenance efforts limestone PT Holcim Indonesia Tbk. Cilacap Plant. The purpose of the study is to determine the condition of post-dredging water quality in terms of physical and chemical factors, to determine the condition of post-dredging water quality in terms of biological factors; and to analyze the relationship between physical, chemical, and biological factors post-dredging shipping lanes limestone around Cilacap Donan River. The research method used was purposive sampling method. The study was conducted from March-May 2013, with five replications. Samples were taken at three stations namely Station 1 (area before dredging), Station 2 (dredging area), and Station 3 (area after dredging). The results showed that water quality conditions of post-dredging chemical in terms of physical factors tend to decrease at station 2 (TSS amounted of 303.6 mgl-1, BOD5 9.806 mgl-1, COD 171.4 mgl-1), followed by station 3 (TSS 268 mgl-1, BOD5 at 18.182 mgl-1, COD is 262.8 mgl-1) and station 1 (TSS 204.4 mgl-1, BOD5 at 12.258 mgl-1, and COD of 252 , 2 mgl-1). Water quality conditions in terms of post-dredging tend to decrease at station 2 (the number of types makrobenthos by 5 species, number of individuals ind/m2 makrobenthos by 147, the number of types of plankton by 11 species and number of individuals of 1,461 ind/l) followed by station 3 (the number of species makrobenthos by 6 species, number of individuals ind/m2 makrobenthos by 180, the number of types of plankton by 12 species, and the number of individual plankton of 1,341 ind / l), and Station 1 (the number of types makrobenthos by 7 species, number of individuals makrobenthos ind/m2 by 327, the number of types of plankton by 12 species, and the number of individual plankton of 1,340 ind / l). In general, the relationship between physical factors, chemical, and biological post-dredging shipping lanes limestone around the same Cilacapmemilikikecenderungan Donan River bahwakondisi declining water quality at Station 2, followed by Station 3 and Station 1.